Structural analysis of Fe-Al coatings applied by gas detonation spraying - Chrostek, Tomasz (Technical Sciences, 2020)
The article analyzes the formation of oxide phases in the structure of intermetallic FeAl coatings applied by gas detonation spraying (GDS). The structural properties of powder charge particles and FeAl coating formed during GDS were determined. The effect of the GDS process on phase changes in FeAl coating applied under controlled conditions was examined. The results indicate that at specific process parameters, FeAl powder particles are strongly oxidized in a hot stream of gases produced during supersonic combustion. Powder particles undergo very strong plastic deformation during the process, and the resulting multiphase coating contains oxide phases that form thin membranes along grain boundaries. The results of structural analyses and microanalyses of chemical composition (SEM/EDS) and phase composition (XRD) indicate that strongly heated FeAl particles undergo surface oxidation during GDS and are transformed into grains (splats) when they collide with a steel substrate. The produced FeAl coating has a multi-layered and multi-phase structure characteristic of the sprayed material, and it contains thin oxide layers, mainly Al2O3.